PWE-024 Early Change in Faecal Calprotectin Predicts Primary Non- Response to Anti-TNFΑ Therapy in Inflammatory Bowel Disease. (17th August 2016) - Pavlidis, P; Gulati, S; Dubois, P; Chung-Faye, G; Tumova, J; Medcalf, L; Choong, LM; Sherwood, R; Bjarnason, I; Hayee, B
Abstract : Introduction: The early identification of primary non-response to anti-TNFα therapy facilitates the timely management of patients with inflammatory bowel disease (IBD). A recent, pilot study to detect prognostic markers of early response to anti-TNFα therapy identified the two genes coding for the calprotectin subunits (S100A8, S100A9) to be among the most highly expressed gene transcripts in non-responders. This study tests the hypothesis that measurements of faecal calprotectin (FCAL) pre- and post- anti-TNFα induction can predict primary non-response in both Crohn's disease (CD) and ulcerative colitis (UC) Methods: Retrospective study of 32 CD and 18 UC patients treated over a two-year period. Outcomes were assessed using Harvey-Bradshaw Index (HBI) or Simple Clinical Colitis Activity Index (SCCAI) (response: drop in HBI/SCCAI >3, remission: HBI < 5, SCCAI <3, steroid free) at 6 months. ΔFCAL was calculated as (FCALpost induction – FCALpre induction)*100/FCAL pre induction. Results: At 6 months, 23 (72%) CD and 10 (56%) UC patients had responded. In remission were 17 (53%) and 5 (28%) respectively. Comparing non-responders to combined response and remission groups, the area under the curve of ΔFCAL to predict outcomes at 6 months was 0.97 for CD and 0.96 for UC. Using ROC analysis, a decrease of 70% returned a sensitivity and specificity of 99% and 96%, respectively (likelihood ratio, LR = 23) in CD. For UC a a decrease of 70% had a sensitivity and specificity of 88% and 86%, respectively (LR = 6). Conclusion: A drop in FCAL < 70% after induction predicts primary non-response to anti-TNFα in both CD and UC. Disclosure of Interest: None Declared